(untitled) (Biological Sciences - PJSIR, 2022)
Sixty seven mutants produced by different physical mutagens were surveyed for antibiotic formation. One mutant out of 18 UV -mutants produced higher antibiotic titres than the initial organism, while in case of the 49 x-rays mutants, none of the mutants produced antibiotic yield more than the parent organism. UV irradiation gave the highest total auxotrophic mutants percentage